1996
DOI: 10.1136/jcp.49.8.667
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation in the normal cervix and in preinvasive cervical lesions.

Abstract: Aims-To characterise further the proliferative compartment of the normal cervix and to document its alteration, if any, in the various grades of cervical intraepithelial neoplasia (CIN), particularly changes to the basal epithelial layer; to hypothesise as to the diagnostic and biological significance of any observed differences. (7 Clin Pathol 1996;49:667-671)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
12
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
(2 reference statements)
9
12
1
Order By: Relevance
“…14 In the present study, it was observed that MIB-1 positive cells were confined to lower one-third of ectocervix in CIN-1 and full thickness in CIN-III. This was in concordance with the study conducted by McCluggage WG et al, Payne S et al and Sansanwal P et al [23][24][25] Payne P et al observed that with increasing grade of CIN, the growth compartment stretched more superficially so that in CIN III almost the full thickness of epithelium was cycling, as shown by Ki-67 immuno-positive cells. 25 In present study, we observed increasing MIB-1 positivity while moving through different severity of CINs, difference being statistically very significant.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…14 In the present study, it was observed that MIB-1 positive cells were confined to lower one-third of ectocervix in CIN-1 and full thickness in CIN-III. This was in concordance with the study conducted by McCluggage WG et al, Payne S et al and Sansanwal P et al [23][24][25] Payne P et al observed that with increasing grade of CIN, the growth compartment stretched more superficially so that in CIN III almost the full thickness of epithelium was cycling, as shown by Ki-67 immuno-positive cells. 25 In present study, we observed increasing MIB-1 positivity while moving through different severity of CINs, difference being statistically very significant.…”
Section: Discussionsupporting
confidence: 81%
“…This was in concordance with the study conducted by McCluggage WG et al, Payne S et al and Sansanwal P et al [23][24][25] Payne P et al observed that with increasing grade of CIN, the growth compartment stretched more superficially so that in CIN III almost the full thickness of epithelium was cycling, as shown by Ki-67 immuno-positive cells. 25 In present study, we observed increasing MIB-1 positivity while moving through different severity of CINs, difference being statistically very significant. This is in concordance with the study of Payne P et al, Bulten J et al, ter Harmsel B et al, Nam JH et al, Conesa-Zamora P et al, Gupta K et al and Sansanwal P et al (Table 6).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, there was no obvious correlation between EZH2 protein levels and the degree of malignancy of the lesions. Whereas the regular detection of high EZH2 protein levels in HPV-positive lesions is fully compatible with EZH2 being a target for oncogenic HPVs, it is notable that we also clearly detected EZH2 expression in the parabasal cells of the cervical mucosa, which represents the main proliferative cell layer in normal cervix (42). Thus, EZH2 expression is unlikely to serve as a novel tumor marker for cervical cancer, in contrast to the situation reported for breast cancer where EZH2 expression is elevated in precancers and cancers but nearly undetectable in normal breast samples (43).…”
Section: Discussionmentioning
confidence: 72%